The foundations of economic method : a Popperian perspective - Boland, Lawrence A. (London ; New York : Routledge, 2003)
This book attempts to change the sidelinng of economic methodology by focusing on current neoclassical research programs, which are beginning to provide a sound theoretical basis for the evolution of economics, game theory, institutions and the market-based system.
Includes bibliogaphical references (p. [309]-323) and indexes
osa 28/10/13
Loans
Keywords: Economics -- Methodology